Income Inequality and Economic Growth: Evidence from the American Data - Ugo Panizza (Inter-American Development Bank, Office of the Chief Economist, 1999)
Cross-country studies have found a negative relationship between income inequality and economic growth. The main problem with the cross-country analyses is the poor quality of the data on income distribution. This paper tests the robustness of the cross-country results to the use of a more accurate cross- state data-set.
Keywords: 330; Einkommensverteilung; Regionale Einkommensverteilung; Wirtschaftswachstum; USA